Prescribing practices of Australian dispensing doctors - Lim, Chee Kiat (David) (Curtin University, 2010)
Background: In response to health workforce shortages policymakers have considered expanding the roles that a health professional may perform. A more traditional combination of health professional roles is that of a dispensing doctor (DD) who routinely prescribes and dispenses pharmaceuticals. A systematic review conducted on mainly overseas DDs’ practices found that DDs tended to prescribe more items per patients, less often generically, and showed poorer adherence to best practice. Convenience for patients was cited by both patients and DDs as the main reason for dispensing. In Australia, rural doctors are allowed to dispense Pharmaceutical Benefit Scheme (PBS) subsidised pharmaceutical benefits if there is no reasonable pharmacy coverage. Little was known about the practices of these Australian DDs.Objectives: To examine the PBS prescribing patterns of dispensing with matched non-dispensing doctors and identify factors that influence prescribing behaviour.Method: A sequential explanatory (QUAN-->qual) mixed methodology was utilised. Firstly, rurality-matched DDs’ and non-DDs’ PBS data for fiscal years 2005-7 were analysed against criteria distilled from a systematic review and stakeholder consultations. Secondly, structured interviews were conducted with a purposive sample of DDs to examine the quantitative findings.Key findings: DDs prescribed significantly fewer PBS prescriptions per patients but used Regulation 24 significantly more than non-DDs. Regulation 24 biased the prescribing data. DDs prescribed proportionally more penicillin type antibiotics, adrenergic inhalants and non-steroidal anti-inflammatories as compared to non-DDs. Reasons offered by DD-respondents highlighted that prescribing was influenced by an awareness of cost to the patients, peer pressure and confidential prescriber feedback provided on a regular basis.Implications: This innovative census study does not support international data that DDs are less judicious in their prescribing. There is some evidence that DDs might reduce health inequity between rural and urban Australian, and that the DD health model is valuable to patients in isolated communities.